Analysis methods of quality and traceability for honey - Czipa, Nikolett; Borbélyné Varga, Mária; Győri, Zoltán (Acta Agraria Debreceniensis, 2008)
Honey is our essential food since ancient times. Thanks to the excellent dietetic and medical features, it has an important function in our nourishment. In Hungary about 25.000 tons of honey are produced each year. Most of the produce, about 80% is exported to different countries of the world. Hungarian types of honey have excellent quality. Through exporting, the prestige and demand of Hungarian honey can be increased. In recent years the adulteration of honey caused many damages to producers and traders. The adulteration of honey is not easy to prove. Thereinafter, we represent several methods, such as oligosaccharide analysis or 13C/12C isotopic ratio analysis, which can identify the artificial substances of honey (for example: corn syrup, high fructose corn syrup) or can help to determine the ratio by which original honey can be identified.